De Novo Construction of Catenanes with Dissymmetric Cages by Space‐Discriminative Post‐Assembly Modification. Issue 18 (9th March 2020) - Li, Pan; Xu, Shijun; Yu, Chunyang; Li, Zi‐Ying; Xu, Jianping; Li, Zi‐Mu; Zou, Lingyi; Leng, Xuebing; Gao, Shan; Liu, Zhiqiang; Liu, Xiaoyun; Zhang, Shaodong
Abstract: Considerable efforts have been made to increase the topological complexity of mechanically interlocked molecules over the years. Three‐dimensional catenated structures composed of two or several (usually symmetrical) cages are one representative example. However, owing to the lack of an efficient universal synthetic strategy, interlocked structures made up of dissymmetric cages are relatively rare. Since the space volume of the inner cavity of an interlocked structure is smaller than that outside it, we developed a novel synthetic approach with the voluminous reductant NaBH(OAc)3 that discriminates this space difference, and therefore selectively reduces the outer surface of a catenated dimer composed of two symmetric cages, thus yielding the corresponding catenane with dissymmetric cages. Insight into the template effect that facilitates the catenation of cages was provided by computational and experimental techniques. Abstract : Best left for later : Catenanes with dissymmetric cages (CDCs) were prepared by first synthesizing imine‐based CSCs (catenanes with symmetric cages) and then selectively reducing the outer surface with the voluminous reductant NaBH(OAc)3 (see picture). Experimental and computational analysis further elucidated the template‐facilitated interlocking mechanism for the construction of three‐dimensional catenanes composed of purely organic constituents.